Appendix 4.17: Marcos Diary Entry, 29 January 1973 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Marcos here seems assured that his cooptation of the judiciary, which began back in 1971 with Lansang , was coming to a close. The specialist in commercial law—his award-winning law school thesis was titled “The Power of the National Assembly to Amend, Alter, of Repeal Corporate Charters Under the Philippine Constitution” (Marcos 1939a, 1939b)—still knew how to make deals in his favor.